ADVANCEMENTS IN EEG TECHNOLOGY AND AI INTEGRATION IN NEUROLOGY - Djurayeva Nigora Rakhbarovna; Ziyovuddinova Samira Jaloliddinovna (Western European Studies, 2025)
This article discusses the role of electroencephalography in the diagnosis of pathologies and diseases of the brain
Keywords: Artificial intelligence; membrane potential; resting potential